1987
DOI: 10.1007/bf01913332
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and mechanism of thermal decomposition of cadmium(II) complexes with substituted thioureas

Abstract: From the thermal decomposition curves of cadmium(II) complexes with substituted thioureas (methyl-, dimethyl-, ethyl-, diethyl-, butyl-, dibutyl-, phenyl-, diphenyl-, acetyl-and benzoylphenylthiourea), the kinetic parameters of the thermal decompositions of these complexes were determined and a decomposition mechanism was suggested. The following thermal stability sequence is given for the Cd(I1) complexes: complexes with alkylthioureas < complexes with phenylthioureas < complexes with acylthioureas.Systemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The nanoscale particles of transition metal coordination polymers have huge thermal stability and tremendous potential applications [1,2]. Various studies have been reported on thermal stability, synthesis, morphological and applications of transition metal organic coordination polymers with derivative of dicarboxylic [3][4][5][6][7], amines [8], aromatic mono/dicarboxylic acid [9,10], substituted thiourea salt and bidentate ligand [11][12][13]. Actually, the supramolecular skeleton of coordination polymer is formed due to the polydentate ligand.…”
Section: Introductionmentioning
confidence: 99%
“…The nanoscale particles of transition metal coordination polymers have huge thermal stability and tremendous potential applications [1,2]. Various studies have been reported on thermal stability, synthesis, morphological and applications of transition metal organic coordination polymers with derivative of dicarboxylic [3][4][5][6][7], amines [8], aromatic mono/dicarboxylic acid [9,10], substituted thiourea salt and bidentate ligand [11][12][13]. Actually, the supramolecular skeleton of coordination polymer is formed due to the polydentate ligand.…”
Section: Introductionmentioning
confidence: 99%
“…In studies on the physical and chemical properties and the structures of solid complexes of transition metal ions with organic ligands, it is customary to investigate the thermal decomposition of these complexes so as to obtain useful data on the metal-ligand bonds [2][3][4] and stability trends. The thermal investigations on some derivatives of amines [5], sulfonamides [6], substituted thiourea salts [7], and complexes of bidentate ligands and others [8][9][10][11][12][13], have already been published.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of literature reports on the thermal analysis investigations of thioureametal ion complexes, publications on the thermal behaviour of these individual materials are very scarce [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%